Guatemala - Klepeis, Alicia, 1971- (2019)
"Engaging images accompany information about Guatemala. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
Tikal -- Location -- Landscape and climate -- Wildlife -- People -- Communities -- Customs -- School and work -- Play -- Food -- Celebrations.
Includes bibliographical references (page 31) and index.
Ages 7-13.
Grades 3-8.
Keywords: Guatemala -- Juvenile literature; Guatemala